The Perceived Effectiveness of Using Mindfulness as a Strategy for Special Educators in Coping with the Stress of their Work Environment - Ciraldo, Lisa (Journal of the American Academy of Special Education Professionals, 2020)
The present study focused on the perceived effectiveness of using mindfulness as a stress-reduction technique among special educators. Studies have shown more focus on using mindfulness with students, versus mindfulness for personal use by educators. Yet, teachers of children with special needs face unique social-emotional challenges in carrying out their roles and their well-being can be compromised as a result. This increased level of stress can lead to job burnout, evidenced by the high attrition rate of special educators. For this study, a quantitative survey was constructed, and then answered completely online and anonymously by special educators and educators in inclusive settings. The results showed that most participants agreed special educators have a high level of stress in their working environment, and that this stress can lead to job burnout. Additionally, over three-quarters of respondents felt mindfulness could help decrease the stress of the work environment yet only one-quarter of respondents stated they had been trained for both mindfulness in the classroom and personal use. Despite any limitations, the results indicate implementing a mindfulness practice among special educators would be a welcome and beneficial method for decreasing the stress and increasing the well-being of these important educators.